2020
DOI: 10.1086/706810
|View full text |Cite
|
Sign up to set email alerts
|

Social Games and Genic Selection Drive Mammalian Mating System Evolution and Speciation

Abstract: Mating system theory based on economics of resource defense has been applied to describe social system diversity across taxa. Such models are generally successful but fail to account for stable mating systems across different environments or shifts in mating system without a change in ecological conditions. We propose an alternative approach to resource defense theory based on frequencydependent competition among genetically determined alternative behavioral strategies characterizing many social systems (polyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 434 publications
0
11
0
1
Order By: Relevance
“…A likely candidate for this green-beard is the Vasopressin receptor, V1aR which evolves mutations when rodents evolve from the promiscuous types of males to purely polygynous types of males. Sinervo et al (27) also found that purely monogamous lineages gave rise to polygynous lineages at a high rate.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A likely candidate for this green-beard is the Vasopressin receptor, V1aR which evolves mutations when rodents evolve from the promiscuous types of males to purely polygynous types of males. Sinervo et al (27) also found that purely monogamous lineages gave rise to polygynous lineages at a high rate.…”
Section: Discussionmentioning
confidence: 95%
“…A likely candidate for this green-beard is the Vasopressin receptor, V1aR which evolves mutations when rodents evolve from the promiscuous types of males to purely polygynous types of males. Sinervo et al (27) also found that purely monogamous lineages gave rise to polygynous lineages at a high rate. These evolutionary transitions between monogamy and polygyny in rodents are linked to a point mutation in a Vasopressin receptor gene [V1aR: (3133)].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, in our study, we failed to find a direct relationship between either habitat type or diet with weaver mating system. Indeed, recent studies on mating system evolution emphasized the link between parental care and social monogamy, which indicates that paternal care and monogamy are coadapted (Lukas and Clutton-Brock 2013;Sinervo et al 2020). Male parental care behaviors can increase female fecundity, which shows that parental conflict may be symmetric between sexes (West and Capellini 2016).…”
Section: Social Organization Beyond Crook's Hypothesesmentioning
confidence: 99%
“…В розвитку ідей видовості особливе місце має посісти концепція еволюції репродуктивних систем, детально досліджена у ссавців у контексті видоутворення (Sinervo et al 2019). Еволюція видовості може бути пояснена через еволюцію систем «охорони репродуктивних систем».…”
Section: ключі до розуміння: автономні репродуктивні системиunclassified